Attitudes towards exercise content on social media and the choice of fitness trainer - Alerić, Nikolina (Annales kinesiologiae (Koper), 2023)
The aim of this study was to: a) investigate and determine gender differences to-wards factors influencing gym-goers’ choice of fitness trainer; and b) to identify and explain gender differences in gym-goers’ attitudes towards social media exercise con-tents (SMEC). For this purpose, a questionnaire was created. The study was conducted on a sample of 50 gym-goers (N1=13 male and N2=37 female), all attending a gym in Split, Croatia. The variable sample consisted of five groups of variables. Test-retest overlap was performed to determine the reliability (88.20%) of the questionnaire. The results showed that the affirmative attitudes were statistically significant in contrast to the non-affirmative attitudes (Wilcoxon Matched Pairs Test, T=250.00, Z=3.60, p<0.001). In addition, male gym-goers generally have a significantly more affirmati-ve attitude towards SMEC than female gym-goers (Mann-Whitney U-test, U=119.50, Z=–2.68, p=0.007). Furthermore, there are gender differences in choosing a fitness trainer based on their appearance; but there are no gender differences in the attitude towards the number of fitness trainers’ followers on social media as an indicator of tru-stworthiness. As this study was specifically concerned with the attitudes of gym-goers, future studies should focus on sports professionals and their attitudes toward this topic.
Keywords: Družbeni mediji; exercise; fitness trainer; gender; odnos; social media; spol; trener fitnesa; Trenerji; vadba